2021
DOI: 10.1155/2021/4425449
|View full text |Cite|
|
Sign up to set email alerts
|

Construction of Clinical Pathway Information Management System under the Guidance of Evidence-Based Medicine

Abstract: This study focuses on clinical pathways guided by evidence-based medicine (EBM). With the clinical pathway as the center, the subjective and objective medical knowledge of medical staff are collected, and a clinical pathway management system guided by EBM is established through a unified process; user demand analysis; main considerations; implementation, evaluation, and monitoring of the clinical path; and dictionary maintenance, to help hospitals fully regulate medical behaviors. Next, the study displays the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…To provide high-quality care, an institution develops, implements, and evaluates clinical pathways (CPs). Clinical Pathways in the care of patients with a specific clinical problem may reduce variations in clinical practice, perform evidence-based practice [44], and optimize resource allocation and cost-effectiveness [45]. Resonating with our findings, team collaboration was often a reported barrier to a successful CP implementation.…”
Section: Cp Significantly Increases Cpat Perceptionsupporting
confidence: 67%
“…To provide high-quality care, an institution develops, implements, and evaluates clinical pathways (CPs). Clinical Pathways in the care of patients with a specific clinical problem may reduce variations in clinical practice, perform evidence-based practice [44], and optimize resource allocation and cost-effectiveness [45]. Resonating with our findings, team collaboration was often a reported barrier to a successful CP implementation.…”
Section: Cp Significantly Increases Cpat Perceptionsupporting
confidence: 67%
“…The whole treatment process will be completed under the guidance of professional doctors and teachers of Chengdu University of Traditional Chinese Medicine in Sichuan, China. This test will be reported following the Comprehensive reporting Test Standard (CONSORT) statement ( 14 ). The flow chart of the trial is shown in Figure 1 , and the schedule for registration, intervention, and evaluation is shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A clinical pathway is an interdisciplinary and integrated management model for clinical diagnosis and treatment, which is a standardized service plan for patients developed in a hospital by a group of multidisciplinary professionals for a particular disease. Its aim is to standardize procedures performed by medical staff, improve the quality and efficacy of medical services, and provide patients with better treatment [15,16]. Clinical pathways are now widely used in the global healthcare industry [17].…”
Section: Introductionmentioning
confidence: 99%